1991
DOI: 10.1113/jphysiol.1991.sp018850
|View full text |Cite
|
Sign up to set email alerts
|

Membrane properties and synaptic responses of rat striatal neurones in vitro.

Abstract: SUMMARY1. A tissue slice containing a section of striatum was cut obliquely from rat brain so as to preserve adjacent cortex and pallidum. Intracellular recordings were.made from 368 neurones, using either conventional or tight-seal configurations.2. Two types of neurone were distinguished electrophysiologically. Principal cells (96%) had very negative resting potentials (-89 mV) and a low input resistance at the resting membrane potential (39 MQ): membrane conductance (10 nS at -65 mV) increased within tens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
188
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(222 citation statements)
references
References 51 publications
33
188
1
Order By: Relevance
“…Striatal spiny neurons had significantly smaller somata than interneurons (15-25 m vs. 30-60 m) and displayed high resting membrane potential ( Ϫ 82 Ϯ 3 mV), action potential discharge with little adaptation during depolarizing current pulses and, when recorded in voltage-clamp mode, a typical current-voltage relationship ( Figure 1A). These electrophysiological properties were similar to those reported previously by our group and by others for medium spiny neurons of the striatum (Kita et al 1984;Jiang and North 1991;Wilson and Kawaguchi 1996;Calabresi et al 1998).…”
Section: Intrinsic and Synaptic Properties Of Striatal Neuronssupporting
confidence: 91%
“…Striatal spiny neurons had significantly smaller somata than interneurons (15-25 m vs. 30-60 m) and displayed high resting membrane potential ( Ϫ 82 Ϯ 3 mV), action potential discharge with little adaptation during depolarizing current pulses and, when recorded in voltage-clamp mode, a typical current-voltage relationship ( Figure 1A). These electrophysiological properties were similar to those reported previously by our group and by others for medium spiny neurons of the striatum (Kita et al 1984;Jiang and North 1991;Wilson and Kawaguchi 1996;Calabresi et al 1998).…”
Section: Intrinsic and Synaptic Properties Of Striatal Neuronssupporting
confidence: 91%
“…Action potential firing showed strong accomodation and was followed by a long-lasting after hyperpolarization (AHP; 3457108 ms duration) (Figure 1b and c). Hyperpolarizing current pulses evoked a prominent voltage sag, characteristic of an I h current (Figure 1b and d) (Jiang and North, 1991;Kawaguchi, 1993). All neurons included in this study showed these properties.…”
Section: Identification Of the Recorded Neuronsmentioning
confidence: 53%
“…Twenty-nine recorded cells had electrophysiological characteristics different from those described for spiny neurons and showed properties that have been attributed previously to large aspiny interneurons (Wilson et al, 1990;Jiang and North, 1991;Kawaguchi, 1992Kawaguchi, , 1993Kawaguchi et al, 1995). In 11 of these 29 LA interneurons the electrophysiological identification was confirmed by a morphological analysis.…”
Section: Physiological and Morphological Properties Of Large Aspiny Imentioning
confidence: 57%
“…When the currents were evoked by hyperpolarizing command steps, there was no detectable time-dependent component. Some of these properties have been described previously both in vivo (Preston et al, 1979;Wilson and Groves, 1980;Calabresi et al, 1990c;Onn et al, 1994a;Xu, 1995) and in vitro (Kita et al, 1984;Calabresi et al, 1990bCalabresi et al, , 1991Calabresi et al, , 1995bJiang and North, 1991;Cepeda et al, 1994) and resemble those reported for intracellularly stained spiny striatal neurons (Preston et al, 1979;Cepeda et al, 1994;Onn et al, 1994b;Calabresi et al, 1995a).…”
Section: Physiological and Morphological Properties Of Spiny Neuronsmentioning
confidence: 64%